DIAGNOSTIC ACCURACY OF SHOCK INDEX AS SCREENING TOOL FOR PRIMARY POSTPARTUM HAEMORRHAGE AFTER CAESAREAN SECTION AMONG WOMEN AT KAWEMPE NATIONAL REFERRAL HOSPITAL -A CROSS-SECTIONAL STUDY. - Lwasa, Joel Njagala Calls; Sekikubo, Musa; Mutyaba, Twaha; Nalwoga, Joannah; Kikonyogo, Joseph (Student’s Journal of Health Research Africa, 2023)
Background: Postpartum haemorrhage is the leading cause of maternal mortality globally and in sub-Saharan Africa. The shock index( ratio of the pulse to systolic pressure) is a quicker and more objective assessment tool for assessing the risk of deterioration as may occur in PPH, before apparent clinical deterioration. The diagnostic accuracy of the shock index in a Ugandan setting is not known. The objective of the study was to determine the sensitivity and specificity, positive and negative predictive values of shock index in the diagnosis of primary postpartum haemorrhage after caesarean section among women delivering at Kawempe National Referral Hospital. Methods: A cross-sectional study design was used. The study was conducted in Kawempe National Referral Hospital among women who were delivered by a caesarean section between 1st January and 31st May 2021. A sample size of 594 was determined using formulae by Buderer. A consecutive sampling technique was used. The research assistants approached 650 participants; while 591 participants were fit for analysis. All participants were subjected to the determination of shock index at different intervals and the change in haematocrit as the gold standard for post-partum haemorrhage. Results: The sensitivity and specificity of the shock index at 2 hours were 40.0 and 82.8 percent respectively at a threshold of 0.8. The sensitivity and specificity were 70.0 and 54.6 percent after 24 hours when the shock index threshold of 0.7 was used. The PPV and NPV were 3.8 and 98.3 percent at 2 hours respectively while 2.6 and 99.1 percent at 24 hours. Conclusion: The shock index is a poor screening tool for diagnosing primary postpartum haemorrhage after caesarean section. Recommendations : Shock index may not be included in routine care of post-operative mothers for early recognition of those at risk of primary postpartum haemorrhage.